Teachers’ knowledge and practice in implementing the thematic approach in pre-school - Zin D.M.M.; Mohamed S.; Kashim M.I.A.M.; Jamsari E.A.; Kamaruzaman A.F.; Rahman Z.A. (IAEME Publication, 2024)
International Journal of Civil Engineering and Technology (IJCIET) Volume 10, Issue 01, January 2019, pp. 1870-1881